Impact of starting material (fresh versus cryopreserved marrow) on mesenchymal stem cell culture. Issue 9 (26th June 2017) - Kaplan, Alesia; Sackett, Katie; Sumstad, Darin; Kadidlo, Dianne; McKenna, David H.
Abstract : BACKGROUND: Mesenchymal stem cells (MSCs) continue to be investigated in multiple clinical trials as potential therapy for different disorders. There is ongoing controversy surrounding the clinical use of cryopreserved versus fresh MSCs. However, little is known about how cryopreservation affects marrow as starting material. The growth kinetics of MSC cultures derived from fresh versus cryopreserved marrow were compared. STUDY DESIGN AND METHODS: Data were reviewed on the growth kinetics of MSCs derived from fresh versus cryopreserved marrow of nine donors. Marrow harvested from each donor was separated into four aliquots (one fresh and three cryopreserved for culture). Data on the date of mononuclear cell cryopreservation/thaw, MSC counts at Passages 1 and 2, MSC doubling, MSC fold expansion, viability (of mononuclear cells and final MSCs), and on flow cytometry markers of mononuclear cells and final MSCs were analyzed for the fresh and cryopreserved marrow groups. RESULTS: In total, 21 MSC lots (seven fresh and 14 cryopreserved) were obtained. The average age of cryopreserved mononuclear cell product was 295 days (range, 18‐1241 days). There were no significant differences between MSC numbers at Passage 1 (p = 0.1), final MSC numbers (p = 0.5), MSC doubling (p = 0.7), or MSC fold expansion (p = 0.7). A significant difference was observed in viability by flow cytometry for both mononuclear cells (p = 0.002) and final MSCs (p = 0.009), with higher viability in the fresh marrow group. CONCLUSION: This study demonstrates that MSCs derived from cryopreserved marrow have the same growth characteristics as fresh marrow–derived MSCs. Further studies are needed to explore potential differences in clinical efficacy.